(untitled) (Materiali di Estetica. Terza serie, 2017)
Theatre, because of its ability to represent through re-staging, would seem to be the quintessential platform for the re-enactment. The Orestea (una commedia organica?) by R. Castelluci and Socìetas Raffaello Sanzio, restaged at Paris Automne Festival in 2015, twenty years after its 1995 world premiere in Prato, is the starting point to reflect on the status of restaging in the theatre. This case study is the occasion to apply W. Benjamin’s philosophical concept of the Jetztzeit to a theatrical context, and to consider also the ‘citational’ value of theatrical re-enactment. These concepts are useful to study not only the re-enactment of the theatrical gest and acting (on which B. Brecht and also W. Benjamin are concerned), but also to consider the practice of re-staging related to the theatrical event conceived in its entirety.